Determinan Gaya Kepemimpinan Kepala Sekolah - Army Yuneti; Marianita Marianita (Journal Of Administration and Educational Management (ALIGNMENT), 2019)
This study aims to describe the leadership style in SMA 5 Lubuklinggau, how the determinants of leadership style principles The research method used is descriptive study, observation and documentation, and this study also uses this type of procedure to develop materials. The results of the study, the environment greatly affects the principal's leadership style, with a good environment can support the application of the principal's leadership style. Conclusion, that research is empirical, education and training, intelligence, skills and environment as capital for principals to be able to apply situational leadership styles, situational leadership styles are very relevant characters and personalities that are different from each other. Keywords: Determinant, Principle Style